Chaos and integrability in -geometry. (August 2021) - Bolsinov, A. V.; Veselov, A. P.; Ye, Y.
Abstract: We review the integrability of the geodesic flow on a threefold admitting one of the three group geometries in Thurston's sense. We focus on the case. The main examples are the quotients, where is a cofinite Fuchsian group. We show that the corresponding phase space contains two open regions with integrable and chaotic behaviour, with zero and positive topological entropy, respectively. As a concrete example we consider the case of the modular threefold with the modular group . In this case is known to be homeomorphic to the complement of a trefoil knot in a 3-sphere. Ghys proved the remarkable fact that the lift of a periodic geodesic on the modular surface to produces the same isotopy class of knots as that which appears in the chaotic version of the celebrated Lorenz system and was studied in detail by Birman and Williams. We show that these knots are replaced by trefoil knot cables in the integrable limit of the geodesic system on . Bibliography: 60 titles.